Comparing Learners’ Perceptions of Learning English via Duolingo and BBC Learning English Platforms - Ratna Widya Iswara; Silvia Catalan Ambag (DUTIES: Education and Humanities International Journal, 2025)
This study explores EFL learners’ perceptions of two widely used digital language learning platforms: Duolingo and BBC Learning English. Drawing on the Technology Acceptance Model (TAM), the research investigates how learners evaluate the platforms in terms of effectiveness, engagement, and usability, as well as their perceived strengths and limitations in developing specific English language skills. Using a qualitative descriptive design, data were collected through semi-structured interviews with ten EFL learners who had experience using both platforms. Thematic analysis revealed that Duolingo was favored for vocabulary and grammar practice due to its gamified and user-friendly design, while BBC Learning English was perceived as more effective for listening comprehension and exposure to authentic language. Learners reported using both platforms strategically, depending on their individual learning goals. The findings highlight the complementary nature of these tools and the importance of aligning digital resources with learners’ preferences and skill development needs. This study contributes to the growing body of research on educational technology in language learning and offers practical implications for educators and developers.